Agentic and Receptive Hope: Understanding Hope in the Context of Religiousness and Spirituality through the Narratives of Salvadoran Youth - Vaughn, Jennifer Medina (Religions, 2022)
Hope contributes to positive development in adolescents, and religious and spiritual contexts may be particularly important for developing and supporting hope. However, extant literature on hope, religion, and spirituality neglects their synergistic relation, leaving questions about how they work together to support development. In this study, we explore how religiousness and spirituality (R/S) inform hope by identifying unique synergies that might be particularly useful in difficult contexts. Multilevel qualitative content analyses of interviews conducted with 18 thriving Salvadoran adolescents (50% female, Mage = 16.39 years, SD = 1.83) involved in a faith-based program provided evidence that the ideological and relational resources associated with R/S informed these adolescents’ agentic and receptive hopes. Agentic hopes, identified through expressed hopeful future expectations, revealed that adolescents held beyond-the-self hopes focused on benefiting three distinct targets: God, community, and family. Youth also described "sanctified hopes", which were hopes focused on fulfilling God’s purposes directly and indirectly. Analyses of receptive hopes, which consider how hope is shaped and empowered by context, revealed that for these youth, hope was experienced in seven key contexts: self, caring adult relationships, family, God, youth development sponsor, social activities, and peers. Implications for fostering hope in R/S contexts within low-to-middle-income countries are discussed.